Una mirada sobre la militancia en los primeros años ’70 a través de la revista Envido (1970- 1973) - Mariana Pozzoni (Nuevo mundo - Mundos Nuevos, 2012)
Between July, 1970 and November, 1973 was published the magazine Envido, directed by Arturo Armada and integrated by a heterogeneous group of persons of the University of Buenos Aires. Identified with the revolutionary Peronism, it proposed to contribute theoretical concepts for the analysis of the national reality. The principal idea was that the dependence was the big problem of the countries of the Third World and that the “national liberation” was a political imperative.The aim of this article is to recover this publishing experience that was defending the project of "national socialism" from a position "movimientista". His study helps to throw light on aspects of the first years of the decade of 1970 that still have not been analyzed in depth to contribute to a more complex look on these years. We depart from the supposition that from this area there was generated spaces of discussion from which one helped to generate a thought that, in a little time, he led the majority of his members to the dissent that took place in the Revolutionary Tendency and that took to the conformation of the Youth Peronist Loyalty between ends of 1973 and beginning of 1974.